PENGEMBANGAN USAHA KECIL BUBUK JAHE DAN KUNYIT MELALUI PENINGKATAN STRATEGI PEMASARAN - Mohamad Bastomi; Agung Suprianto; Mujahid Ansori; Moh. Fikri Alghifari; Faiza Nur Afiyah; Farah Fatimatus Zahro; Mega Pramesti Priyanti; Nabila Nafisah Rahmawati; Siti Ni’matul Umah; Zakia Bahama Putri Hawa; Andyka Rendy Indra Prasetya (As-Sidanah, 2022)
This small business of ginger and turmeric powder is a business undertaken by one of the housewives in Krajan hamlet. This ginger and turmeric powder business has problems related to branding and marketing. This causes this business to be relatively unable to develop. This service aims to improve the quality of instant ginger and turmeric powder business. The method used in this service is direct and gradual socialization and assistance. This community service is able to develop and improve the quality of small businesses of instant ginger and turmeric powder, so that in increasing product competitiveness, these businesses can excel and deserve to be recognized in national and international markets.